36 MEDICAL AND NEUROLOGIC PROBLEMS IN FEMALES WITH THE FRAGILE X PREMUTATION. Issue 1 (1st January 2007) - Tartaglia, N. R.; Coffey, S.; Cook, K.; Soontarapornchai, K.; Bronsky, H.; Hagerman, R. J.
Abstract : Purpose of Study: Women with the fragile X premutation were originally thought to be unaffected by the CGG repeat (55-200). Recent research shows that women with the premutation have a higher rate of premature ovarian failure and osteoporosis than the general population and are also affected with the fragile X tremor ataxia syndrome (FXTAS). The purpose of this study is to evaluate the medical problems and neurologic examination in a large group of women with the fragile X premutation compared with controls to identify other medical problems that may be related to the carrier state. Methods: All females seen in the Fragile X Research and Treatment Center at UC-Davis with the premutation were included in this study ( n = 139). Control subjects ( n = 68) included family members of fragile X families and females recruited from the Sacramento area without the premutation age-matched to the premutation group. All subjects underwent a standardized detailed medical history, review of systems, and examination including comprehensive neurologic testing. Prevalence of medical and neurologic problems were compared between the premutation group and the control group. Results: The study groups included 139 women with the fragile X premutation (18 FXTAS, 121 non-FXTAS) and 68 controls. In the premutation group, 16% had premature ovarian failure, consistent with previous reports in the literature in this population. Results also showed many other medical problems and physical examination findings in the premutation group with significantly higher prevalence than the typical population and controls, including hypothyroidism (22.5%), lupus (3%), optic neuritis (3.7%), multiple sclerosis (2%) fibromyalgia (12.4%), muscle pain (33%), and peripheral sensory deficits (12%) ( p < .05). In women with FXTAS, 50% had thyroid disease compared with 6% in controls. Conclusions: Women with the fragile X premutation are more likely to have thyroid disease, MS symptoms, fibromyalgia, and neurologic findings such as peripheral sensory deficits, even if they do not meet the diagnostic criteria for FXTAS. Women with FXTAS have the characteristic symptoms of FXTAS (tremor, ataxia), in addition to higher rates of thyroid disease and cardiovascular problems. Thyroid screening and close neurologic follow-up are recommended for all women with the fragile X premutation.